Effects of Whole-Body Vibration Training Combined With Cyclic Hypoxia on Bone Mineral Density in Elderly People - Camacho-Cardenosa, Marta; Camacho-Cardenosa, Alba; Burtscher, Martin; Brazo-Sayavera, Javier; Tomas-Carus, Pablo; Olcina, Guillermo; Timón, Rafael (Frontiers in Physiology, 2019)
Prevention and treatment of osteoporosis are an issue of great concern in public health so that the increase/maintenance of whole-body bone mineral density (BMD) is clinically relevant and could reduce the financial burden. Whole-body vibration (WBV) has been recently proposed as a potential alternative to bone stimulation, which combined with therapies, could provide a new treatment for osteoporosis prevention. In this sense, moderate cyclic hypoxia protocols may help to restrain osteoclastic activity and/or stimulate osteoblastic activity, enhance the effects of whole-body vibration alone. So, the present study investigated the effects of cyclic hypoxic exposure combined with WBV training on BMD of the elderly. Healthy elderly persons (n=30) were randomly assigned to a (1) Hypoxia-Whole Body Vibration group (HWBV; n=10), (2) Normoxic-Whole Body Vibration group (NWBV; n=10) or (3) Control group (CON; n=10). During 18 weeks, HWBV performed WBV treatment under normobaric hypoxic conditions (16.1% FiO2). A vibration session included 4 bouts of 30 s (12.6 Hz - 4 mm) with 1 min rest between bouts. NWBV performed the same vibration treatment as HWBV but under normoxic conditions. Whole-body and proximal femur BMD (g·cm-2) were measured using dual-energy X-ray absorptiometry. Two-way ANOVA indicated a borderline significant (p=0.07) time x group interaction for total BMD; post-hoc analysis revealed a slight but significant (p=0.021) increase of BMD after treatment in the HWBV group. In conclusion, 18-week WBV training with hypoxic stimuli has shown positive effects for the participants of the current study. As changes did not differ significantly between groups, future large-scale studies will be necessary to confirm these findings.